The effect of music listening on emotional responses to compassionate scenes : the role of stimulus type and trait empathy - Gurrola, Adriana Zamudio (2018)
The perception of emotion is not something we experience using isolated sensory modalities. Research has shown that auditory and visual domains influence each other in the processing of affective stimuli. Nevertheless previous studies have looked at the effects of these influences while dealing with only a few basic emotions, such as happiness, sadness, fear or anger. It is yet to be observed whether similar interactions can be observed for more complex emotions. The present study tested whether listening to music could influence people’s emotional response to a visual cue for a higher-level emotion such as compassion by evaluating the effects that different types of music had on compassionate scenes as opposed to noncompassionate ones. It also set out to explore the role that trait empathy and musical preference played in accounting for individual differences. To achieve this, ratings on Valence, Arousal and Compassion for compassion-inducing (CI) and non-compassion-inducing (NCI) pictures during four different music and silence conditions were collected. As a measure for empathy the Empathic Concern subscale of the Interpersonal Reactivity Index was obtained as well as a liking score for each of the music pieces. Results showed that High-Valence+Low-Arousal music significantly increased the compassionate response to both types of pictures, whereas Low-Valence+Low-Arousal and Low-Valence+High-Arousal music showed virtually no effect. High-Valence+High-Arousal music, although preferred by most participants, decreased the compassionate response to affective pictures and increased it for neutral stimuli. More empathic participants displayed stronger overall feelings of Compassion and also showed more variability in those ratings between the music conditions, particularly when rating NCI pictures.